Increased performance uncertainty in children with ADHD?: Elevated post-imperative negative variation (PINV) over the ventrolateral prefrontal cortex - Werner, Janina; Weisbrod, Matthias; Resch, Franz; Rößner, Veit; Bender, Stephan (Behavioral and brain functions, 2011)
We aimed to investigate the influences of attention deficit/hyperactivity disorder (ADHD) on response evaluation, as reflected by the postimperative negative variation (PINV), a slow event-related potential.
Gesehen am 12.12.2022